The many faces of crime for profit and ways of tackling it - Duyne, Petrus C. van; Harvey, Jackie; Antonopoulos, Georgios; Lampe, Klaus von (Cross-border Crime Colloquium, 2017)
The national diversity of Europe is reflected in the diversity of its criminal landscape and history. From the north of Scotland to Ukraine one finds different focal points and patterns of crimes and criminal entrepreneurs. This does not necessarily lead to a corresponding reaction of the authorities. Some responses are the result of a gradually developed form of cross-border cooperation, as is the case between Poland and Germany, other authorities appear carried away with emotional decision making and an inflexible political correctness as is observed in the field of the sex service industry. In another country, in the adjacent field of child trafficking, we find the converse: no response as victims are not labelled as such. And no victim label, no criminal law policy. 0Where the interactions between the upper- and underworld come into sight, this volume presents the reader with a select picture gallery of criminal faces: from corrupt football to remarkable criminal finances in Ukraine, to fraud and criminal abuse in the informal or quack health sector. Naturally, each face has its own pretences in order to hide its criminal background, be it large scale cannabis growing in the Netherlands or organised cybercrime from Romania to all countries in Europe.0Indeed, the criminal portrait series in this volume shows that criminal Europe does not lead to a boring uniformity, despite the fear of globalism. This volume contains the seventeen peer-reviewed contributions of 26 authors presented in 2016 at the Cross-border Crime Colloquium held at Northumbria University, Newcastle